PENGARUH KESEHATAN DAN KESELAMATAN KERJA, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. INTIDAYA DINAMIKA SEJATI - Daffa, Rafillah; Azhad, M Naely; Puspitadewi, Ira (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research aims to determine the influence variables of occupational health and safety (X1), work compensation (X2), and work motivation (X3), on employee performance (Y) at PT. Intidaya Dinamika. PT. Intidaya Dinamika Sejati is a company that operates in the fields of Design, Engineering and Service in the industrial and general business sectors. If you look at its business activities, this company is a service company, because the main activity of this company is machine servicing. This research uses quantitative research with a descriptive approach. The population in this research is 120 employees and the sample taken was 96 employees using a simple random sampling technique and determined using the Slovin formula. Data collection methods using questionnaires, observation and interviews. The results of this research at a significance level of 0.05% can be partially concluded that work health and safety, work compensation, and work motivation have a significant effect on the performance of PT employees. The Core of True Dynamics. This can be seen based on the results of the coefficient of determination test (R2) that the three independent variables influence the performance of PT employees. Dinamika Sejati's core power is 91.4% and the remaining 8.6% is influenced by other variables such as workload, leadership style and work discipline.